2019
DOI: 10.1353/hpu.2019.0019
|View full text |Cite
|
Sign up to set email alerts
|

The Usage and Associated Factors of Alternative Tobacco Products among School-going Youth in Central Appalachia

Abstract: Objective: To examine alternative tobacco product (ATP) use and associated factors among middle school students in Appalachian Tennessee. Method. Data (2015-2016; N=573) from school-based tobacco surveys in 11 middle schools in Appalachian Tennessee were analyzed. Multiple logistic regression model described factors associated with ATP use. Results. Over one-tenth (13.2%) of participants have ever used ATPs. Approximately 9%, 7%, 6%, and 2% of participants have ever used e-cigarettes, cigarettes, smokeless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…ENDS use among USA youths has surpassed all CTPs since 2014 [2,19,28]. However, studies involving youth in high-risk environments such as distressed rural areas that predispose youth to tobacco use and make them vulnerable to initiate ENDS use are sparse [10,[55][56][57][58]83]. This study explored the use of ENDS among students in an ARC-designated, distressed, rural county in Appalachian Tennessee in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…ENDS use among USA youths has surpassed all CTPs since 2014 [2,19,28]. However, studies involving youth in high-risk environments such as distressed rural areas that predispose youth to tobacco use and make them vulnerable to initiate ENDS use are sparse [10,[55][56][57][58]83]. This study explored the use of ENDS among students in an ARC-designated, distressed, rural county in Appalachian Tennessee in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Despite high Appalachian youth tobacco use rates, few studies have examined patterns of use and associated factors. One study, using data collected in the Central Appalachian region in 2015–2016, reported that over 10% of middle schoolers had used alternative tobacco products, such as hookah and cigarillos 30 . Another, using data from 2016 in the same region, found that e-cigarettes were the most commonly used product among high schoolers and that many e-cigarette users also consumed one or more additional tobacco products 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The rate of tobacco use among Appalachian Tennessee residents is higher than that of the State of Tennessee and the entire nation [47,48], which is why the region is part of Truth Initiative-designated "Tobacco Nation" [22]. The participants in the study were generally aware of these disparities in the usage of tobacco products across demographic subgroups and geographic areas.…”
Section: The Burden Of Tobacco Use In Appalachian Tennessee Comparedmentioning
confidence: 99%